2021
DOI: 10.1186/s12968-021-00776-7
|View full text |Cite|
|
Sign up to set email alerts
|

The association of reduced left ventricular strains with increased extracellular volume and their collective impact on clinical outcomes

Abstract: Background Myocardial fibrosis and left ventricular (LV) longitudinal strain are independently associated with adverse clinical outcomes. However, the relationship between tissue properties and strain indices as well as their collective impact on outcomes are yet to be fully elucidated. We aim to investigate the relationship between LV global longitudinal strain (GLS), global circumferential strain (GCS) and global radial strain (GRS) with extracellular volume (ECV) and their collective impact.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…GRS was the strain parameter with the highest range of variance and also the only parameter showing significant bias from pooled medians. This is in line with previous studies, which already identified GRS as the least robust parameter 9 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…GRS was the strain parameter with the highest range of variance and also the only parameter showing significant bias from pooled medians. This is in line with previous studies, which already identified GRS as the least robust parameter 9 …”
Section: Discussionsupporting
confidence: 93%
“…Strain imaging and global longitudinal strain (GLS) in particular have since been analyzed in multiple studies to evaluate the prognosis for ischemic as well as nonischemic cardiomyopathies. [6][7][8][9][10] However, as the foundation (ie, the cine sequences) evolved, the postprocessing algorithms had to be constantly reevaluated. Previous single-software studies have shown an excellent correlation between FT-strain values derived from Cine and CS sequences; however, most studies revealed a consistent underestimation of CS-derived strain values.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that strain assessment by FT correlates significantly with the ECV burden in patients with non-ischemic cardiomyopathies ( 37 ), potentially being a non-contrast dependent tissue marker for myocardial fibrosis. Strain values can also aid in risk stratification with decreased strain values being associated with worse outcomes ( 38 , 39 ). Similar results have been observed by the application of strain-encoded magnetic resonance (SENC) tagging acquisitions ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 162 patients were recruited of whom 141 could be included for analysis (median age [interquartile range (IQR)], 45 (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56); 83 women; 34/141 sCov, 43 (37-52); 19 women; 63/141 pCov, 52 (39-58); 43 women; 44/141 CovVac, 43 (32-56), 23 men; and 44 HC, 41 (28-52); 24 women; Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation